Impacts of plant invasive species on local farming communities around Mulanje Mountain Forest Reserve, Malawi (Journal of Sustainability, Environment and Peace, 2019)
This paper sought to examine the impacts of plant invasive species on communities living around the Mulanje Mountain Forest Reserve (MMFR). 30 respondents were selected using systematic sampling from five villages around the forest. The chi-square was used to test the hypothesis that the plant invasive species had no positive impacts on the local farming communities neighbouring the forest reserve. The findings indicated that plant invasive species had more of negative impacts on communities neighbouring the forest than positive impacts. The results showed that the communities identified reducing agricultural yields as the main threat followed by competition with medicinal plants and firewood. In terms of recommendations, education and awareness was found to be the key for addressing this issue.
Keywords: Invasive species; threats; communities; education